Expert-derived indicators for evaluating design thinking prototypes in teacher education - Mary Cris J. Go; Jovelyn G. Delosa; Christine C. Royo (International Journal of Evaluation and Research in Education (IJERE), 2026)
Evaluating design thinking prototypes in teacher education remains challenging due to the absence of standardized and theory-aligned evaluation criteria. Existing assessment practices are often inconsistent and insufficiently aligned with the process-oriented nature of design thinking–based research. This study aimed to develop expert-derived indicators to inform the construction of a prototype evaluation instrument for teacher education research. Using a qualitative instrument development approach, a focus group discussion (FGD) was conducted with research advisors and panel members experienced in evaluating undergraduate and graduate research outputs. Data were analyzed using Braun and Clarke’s reflexive thematic analysis, resulting in six evaluation domains: problem alignment and functional relevance, novelty and intellectual property integrity, standardization of evaluation practices, alignment with design thinking processes, feasibility and sustainability, and demonstration of research and professional competencies. These domains were operationalized into a pool of observable indicators representing key dimensions of prototype quality. The resulting domains provide initial content validity evidence for the development of a standardized prototype evaluation instrument, supporting subsequent content validation and psychometric testing. The findings offer an expert-informed evaluation framework that contributes to more rigorous, transparent, and consistent assessment of design thinking prototypes in teacher education and higher education research.